1991
DOI: 10.1111/j.1559-1816.1991.tb00451.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceiving Age and Attractiveness in Facial Photographs1

Abstract: In two experiments, 492 male and female subjects from three different age groups estimated the age of adult men and women on the basis of photographs and provided attractiveness ratings of the stimulus persons. With regard to the age estimates there was almost perfect agreement between the mean judgments of the different groups, and there was high consensus among the individual judges within each group. For each single picture, however, there was high variability in the age estimates; and although the estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
75
2
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 16 publications
9
75
2
1
Order By: Relevance
“…Henss (1995a, b) also noted this point in his study, and attributed it to an "attractiveness bonus" effect for young females. As this claim is supported by a large body of literature (Henss, 1991(Henss, , 1992, it is plausible in explaining the effect of stimulus sex on variance in ratings, but it cannot be denied that the poverty of the quality of male line drawings also affected participants' judgements. Henss noted that males with low WHR's were considered particularly unattractive.…”
Section: Discussionmentioning
confidence: 97%
“…Henss (1995a, b) also noted this point in his study, and attributed it to an "attractiveness bonus" effect for young females. As this claim is supported by a large body of literature (Henss, 1991(Henss, , 1992, it is plausible in explaining the effect of stimulus sex on variance in ratings, but it cannot be denied that the poverty of the quality of male line drawings also affected participants' judgements. Henss noted that males with low WHR's were considered particularly unattractive.…”
Section: Discussionmentioning
confidence: 97%
“…Dehon and Brédart (2001) found age estimates for male faces to be more precise than age estimates for female faces. Moreover, research on perceived attractiveness shows stronger negative correlations between perceived age and attractiveness for women than men (Henss, 1991). Thus, perceived age may be more important for women, and women may be willing to take more efforts to look younger.…”
Section: Role Of Age Gender Expression Of the Target Face And Intementioning
confidence: 99%
“…Regarding group characteristics, the precision with which the age of a face is estimated seems to depend on the age of the depicted person. In particular, overestimating the age of young faces (i.e., estimating the face as older than the person's actual age) appears to be a common phenomenon (Henss, 1991;Sörqvist & Eriksson, 2007;Vestlund, Langeborg, Sörqvist, & Eriksson, 2009;Willner & Rowe, 2001). There is also some evidence that the age of older persons is more likely to be underestimated than that of younger persons (e.g., Henss, 1991;Vestlund et al, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies on adults' facial age judgments have focused on accuracy in judging facial age, which have shown that adults are generally accurate in judging the age of own-race faces (Burt & Perrett, 1995;George & Hole, 1995Henss, 1991). Other studies have also focused on the different facial cues that adults use to judge age, such as craniofacial shape, amount of cranial hair, presence or absence of wrinkles, appearance and height of internal facial features, and skin tone (Burt & Perrett, 1995;Fink, Grammer, & Matts, 2006;George & Hole, 1995, 1998Gross, 1997;Mark et al, 1980;Pittenger & Shaw, 1975;Wogalter & Hosie, 1991).…”
mentioning
confidence: 99%